Dairy imports into sub-Saharan Africa and their policy implications - Massow, V.H. von (1985)
Describes the development of African dairy imports and highlights the factors that have caused increases of imports in recent times, particularly population growth, urbanisation, changes in prices, increased incomes, availability of foreign exchange, and food aid; discusses the role of national policies with their objectives, instruments, and possible effects. Includes a brief assessment of how further research may help solve some of the problems that have arisen.